INOVASI MODEL BISNIS UKM DITINJAU DARI BERBAGAI PERSPEKTIF - Fauzan, Yuda; Kholid Mawardi, Mukhammad; Iqbal, Mohammad (Profit: Jurnal Adminsitrasi Bisnis, 2021)
The purpose of this paper is to focus on a discussion that discusses Business Model Innovation. Based on preliminary research, the authors develop a proposition whereby the application of BMI in SMEs can be viewed from the degree, typology, and drivers. This paper examines the research published either experimentally, empirically, or conceptually with the theme of Business Model Innovation. The research was obtained from several journal portals such as Emerald Insight, Elsevier, and Research Gate for later criticized. This paper discovers BMI research which is still limited to the realm of large companies as its object, while in the realm of SMEs it is still rarely done. Meanwhile, BMI research at the SME level is expected to be able to boost the performance of SMEs in conducting their business, so that it becomes more structured and can compete in a wider realm. This paper discusses that future research can analyze aspects of innovation, innovation typologies, and factors driving innovation, and further research is expected to add other aspects that might emerge the next day that discuss the context of SMEs in Indonesia.